Effects of budlein A on human neutrophils and lymphocytes - Carollinie Dias KNOB; Milena SILVA; Thaís Helena GASPAROTO; Carine Ervolino OLIVEIRA; Nádia Ghinelli AMÔR; Nilton Syogo ARAKAWA; Fernando Batista COSTA; Ana Paula CAMPANELLI
ABSTRACT Sesquiterpene lactones (SLs) are the active constituents of a variety of medicinal plants used in traditional medicine for the treatment of inflammatory diseases and other ailments. Objective In this study, we evaluated whether budlein A modulates the activation of innate and adaptive immune cells such as neutrophils and lymphocytes. Material and Methods Our research group has investigated several plant species and several compounds have been isolated, identified, and their medical potential evaluated. Budlein A is a SL isolated from the species Aldama buddlejiformis and A. robusta (Asteraceae) and shows anti-inflammatory and anti-nociceptive activities. Advances in understanding how plant-derived substances modulate the activation of innate and adaptive immune cells have led to the development of new therapies for human diseases. Results Budlein A inhibited MPO activity, IL-6, CXCL8, IL-10, and IL-12 production and induces neutrophil apoptosis. In contrast, budlein A inhibited lymphocyte proliferation and IL-2, IL-10, TGF-β, and IFN-γ production, but it did not lead to cell death. Conclusions Collectively, our results indicate that budlein A shows distinct immunomodulatory effects on immune cells.